(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Carpal tunnel syndrome (CTS) is the most common nerve entrapment, electrodiagnostic studies are a valid and reliable means of confirming the diagnosis. Objectives:The study aims to find a correlation between the presence of Tinel’s sign and Phalen’s maneuver and the degree of severity of the CTS and to compare it with severity of nerve conduction study of median nerve. Methods:The study involves 133 patients (102 females and 31 males) with CTS, all were examined for Phalen’s maneuver and Tinel’s sign and median and ulnar nerves electro physiological study in Al-Yarmouk Teaching Hospital and the Neurosciences Hospital in Baghdad between January 2010 and January 2011. Their ages ranged between (19-87) years. The patients were grouped into mild, moderate and severe CTS according to modified Padua scale of CTS severity. Statistical correlation was done using one way Anova test. Results:Positive Tinel’s sign was seen in 25% and positive Phalen’s maneuver in 28%, coexistent Tinel’s sign and Phalen’s maneuver positive at the same time were seen in 47%. Total Tinel’s sign was72% and total patients who had positive Phalen’s sign was 75%. Mild, moderate and severe CTS were seen in 38%, 41% and 21% out of the total number of the studied patients. Conclusion:The study didn’t find association between severity grading and provocative test, added to negative provocative tests in high percentage of patients. These results mandate the use of electrophysiological examination for the diagnosis of carpal tunnel syndrome and assessment of severity. Keywords:Carpal tunnel syndrome, Tinel’s sign, Phalen’s maneuver